The Architecture value engine: Measuring and delivering sustainable SoC improvement - Carballo, Juan-Antonio; Bangqi Xu (Digest of technical papers - IEEE/ACM International Conference on Computer-Aided Design, 2016)
The value of semiconductor-based systems continues to increase rapidly especially when considering the cost associated with building it. As such, Moore's Law has become a law associated broadly with value growth instead of pure performance growth. While semiconductor nodes continue to provide value albeit at a slower rate, it is design factors that ensure value is indeed filtered down to the final product. In this paper we assess the impact of architecture improvements in the value trends associated with key industry drivers such as mobile (smartphone) systems. We attempt to measure the delivered value and to understand the contribution of Architecture as a fundamental engine for improvement in coming decades.